TRANSFORMATION OF RESTORATIVE JUSTICE IN THE INDONESIAN CRIMINAL JUSTICE SYSTEM TOWARDS A JUST AND REHABILITATIVE LEGAL APPROACH - Tengku Muhammad Reza Fikri Dharmawan; Ismaidar, Ismaidar; Tamaulina Br. Sembiring (PT. Sinergi Legal Publisher, 2025)
Restorative Justice (RJ) offers a new paradigm in the Indonesian criminal justice system that focuses on restoration, reconciliation, and rehabilitation rather than just punishment. Although various regulations such as Attorney General Regulation Number 15 of 2020, Circular Letter of the Chief of Police Number SE/8/VII/2018, and PERMA Number 2 of 2012 have supported the implementation of RJ, this approach still faces various challenges. Inconsistent regulations and minimal capacity of law enforcement officers are the main obstacles in the effective implementation of RJ principles. This lack of integration of regulations creates legal uncertainty, while the lack of training and technical guidance hinders officers from managing conflicts fairly and inclusively. This study analyzes the importance of RJ transformation through the establishment of an independent Restorative Justice Law. This law is expected to unify various sectoral regulations, expand the scope of RJ implementation, increase accountability, and equip officers with adequate capabilities to implement RJ consistently. With a clear legal basis, the Indonesian criminal justice system can move towards a more just and rehabilitative approach, in accordance with the values ​​of Pancasila. The research results recommend the establishment of an integrated legal framework, intensive training for law enforcement officers, and public education to improve public understanding of RJ. Thus, RJ can be an effective transformation tool in realizing a humanistic and sustainable criminal law system.